Portraits of Peasant Resistance to Mining Extractivism: An Analysis of the Documentary “Daughter of the Lake (2015)” - Luna Paredes, Andrea (2024)
The article analyzes the film “Hija de la laguna” (2015) as a paradigmatic case of socio-environmental documentary, whose purpose is to mark a political position through the image and audiovisual treatment in order to position itself in favor of the environmental struggles, in this case, against mining extractivism, as it seeks to portray peasant demands, taking into account the point of view of activist Nélidad Ayay.